Analysis Of The Suitability Of Fire Handling With Active Fire Protection In Yaperjasa Senior High School In 2020 - Nurul, Windi (Universitas Pembangunan Nasional Veteran Jakarta, 2020)
Fire starts with burning until it cannot be controlled. Fire can has many effects in fatalities, material damage, and business. Based on data from National Disaster Management Agency the fire that occurred in Indonesia in 2012 until 2018 with a total of 486 incidents. According to Kepmen PU No. 10/2002, every building must completed the fire safety protection including an active fire protection system.This study used descriptive design with mix method using an observational approach. This research instrument using a checklist and interview sheets. The purpose of the research is to determine the suitability level of active fire protection in Yaperjasa senior high school in 2020 than the result will be compared based on several standards preference such as Permen PU No.26/2008, SNI 03-3989-2000, SNI 3985-2000, SNI 1745-2000, Permen PU No.20/2009 dan NFPA.From the result of research showed the suitability level of the active fire protection system in Yaperjasa senior high school only has existing components only fire extinguisher with a score 73.3%. This level means it has quite good suitability, but there are still many components that are not available such as fire hydrants, sprinklers, standpipe systems, manual call point, fire alarm adan fire detectors.Keywords: Fire, suitability, active fire protection